Produção e qualidade da batata-doce em função de biofertilizante e fontes de nitrogênio - Bandeira, Natália Vital da Silva (2016)
Studies which aimed the increase of yield and root qualities of sweet potato can constitute in important tools to improve social condition in the Northeast Region, because it is one most important vegetables. With the aim to evaluate the effect of bio-fertilizer concentrations and sources of N through production and quality of sweet potato, Campina crop, had been installed an experiment in the Federal University of Paraiba, Areia – PB, in an experimental sketching in randomized blocks factorial scheme 5 x 2, being 5 concentrations of bio-fertilizer (0, 10, 20, 30 and 40%) and two sources of nitrogen (ammonium sulfate and urea), with four repetitions. It had been evaluated the length and diameter, average mass, total and commercial productivity, production and root numbers per plant-1, green mass of plant air-1, dry matter of plant air-1, organic matter of soil and foliar levels of N, P and K, glucose levels, starch and ashes, anthocyanin levels, protein and humidity. According to results, it had been seen that bio-fertilizer influenced in a positive way all features in sweet potato, but it had difference relationing to nitrogen sources. Length, media average, production and root plant number -1 and ashes level in the roots were bigger with the usage of ammonium sulfate and urea. Green and dry matter increased with evaluation periods and with the usage of nitrogen in two sources. Organic matter level on soil after crop was bigger when urea was used. Foliar levels of N, P and K were suitable to sweet potato, despite nitrogen sources. Starch levels, protein, anthocyanins, humidity were suitable. Production and quality increased with the usage of bio-fertilizers 20-22%. Ammonium sulfate is a nitrogen source very recommended, bio-fertilizer and N increased soil organic matter level and foliar levels of N, P and K increased functioning of the treatments.